Factors influencing tax compliance and use of online tax systems in Thika town - Muchiri, A. W. (Strathmore University, 2020)
Tax has been and remains to be the main source of revenue for the government of Kenya. Over time, the Kenyan government, through the Kenya Revenue Authority, has put effort in increasing amounts receivable through reducing the costs incurred in collecting taxes and increasing the tax base. For a tax, system to be adequate, compliance by taxpayers should to be high. Akubo et al (2016) stated that tax compliance is the process by which taxpayers, meet their tax obligations by submitting the relevant documents and any other information needed by the revenue authority. It also involves timely filing of returns by taxpayers. It is important for a taxpayer to understand his tax obligations, the laws involved and the procedures and be literate in order to avoid problems of underpaying and overpaying. The revenue authority should play a role in ensuring that adequate resources is directed towards taxpayers to enable them understand more how to meet their obligations.
Full - text undergraduate research project